Monounsaturated and polyunsaturated fatty acids concerning prediabetes and type 2 diabetes mellitus risk among participants in the National Health and Nutrition Examination Surveys (NHANES) from 2005 to March 2020 - Jiang, Susu; Yang, Wenhan; Li, Yanmei; Feng, Jingying; Miao, Junjie; Shi, Hongmei; Xue, Hongmei (Frontiers in Nutrition, 2023)
Objective: Unsaturated fatty acids (UFA) may be related to glycometabolism. While associations between UFA intake (especially their subtype) and prediabetes or type 2 diabetes mellitus (T2DM) need to be fuether studied. Here, we aimed to evaluate the potential relation of UFA with prediabetes and T2DM.: A total of 16,290 adults aged over 18 years from the National Health and Nutrition Examination Survey (NHANES) from 2005 to March 2020 were included in the present analysis.Dietary intake were assessed by two-day 24-hour dietary recalls and daily intake of total monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA), four specific fatty acids of MUFA, seven specific fatty acids of PUFA were calculated. Prediabetes and T2DM were diagnosed by fasting glucose, glycohemoglobin, and self-report medication or insulin. Rao-Scott modified chi-square tests, Taylor series linearization method, and multivariable logistic regression analyses were applied to analyze the associations of dietary MUFA and PUFA intake with diabetes risk. This is a provisional file, not the final typeset article Results: Of the participants, 44.34% had prediabetes, and 13.16% had T2DM patients. From multivariate analysis, we found that intake of MUFA, PUFA, and some subtypes were negatively associated with the risk of prediabetes and T2DM in Americans. Compared to adults in the lowest tertile, those in the highest MUFA (PUFA) tertile had an approximately 50% (49%) and 69% (68%) lower risk of prediabetes and T2DM, respectively. Moreover, the effects of the subtypes of MUFA and PUFA on prediabetes and T2DM were different. Higher intakes of MFA 18:1, MFA 20:1, PFA 18:2, and PFA 18:3, and highest tertile intake of MFA 16:1 and PFA 20:4 was related to lower risk of prediabetes and T2DM. Similarly, the effects of MUFA, PUFA, and subtype on prediabetes and T2DM varied among different age groups, being weakened along with age.Our study suggested that total MUFA and PUFA intake might be essential in preventing prediabetes and T2DM, especially T2DM for Americans. However, this protective effect may be decreased with increasing age. Moreover, the effects of the specific UFA on prediabetes and T2DM need further consideration.